A multi-adaptive framework for the crop choice in paludicultural cropping systems - Silvestri, Nicola; Giannini, Vittoria; Dragoni, Federico; Bonari, Enrico (Italian Journal of Agronomy, 2017)
The conventional cultivation of drained peatland causes peat oxidation, soil subsidence, nutrient loss, increasing greenhouse gas emissions and biodiversity reduction. Paludiculture has been identified as an alternative management strategy consisting in the cultivation of biomass on wet and rewetted peatlands. This strategy can save these habitats and restore the ecosystem services provided by the peatlands both on the local and global scale. This paper illustrates the most important features to optimise the crop choice phase which is the crucial point for the success of paludiculture systems. A multi-adaptive framework was proposed. It was based on four points that should be checked to identify suitable crops for paludicultural cropping system: biological traits, biomass production, attitude to cultivation and biomass quality. The main agronomic implications were explored with the help of some results from a plurennial open-field experimentation carried out in a paludicultural system set up in the Massaciuccoli Lake Basin (Tuscany, Italy) and a complete example of the method application was provided. The tested crops were Arundo donax L., Miscanthus×giganteus Greef et Deuter, Phragmites australis L., Populus×canadensis Moench. and Salix alba L. The results showed a different level of suitability ascribable to the different plant species proving that the proposed framework can discriminate the behaviour of tested crops. Phragmites australis L. was the most suitable crop whereas Populus×canadensis Moench and Miscanthus×giganteus Greef et Deuter (in the case of biogas conversion) occupied the last positions in the ranking.